(untitled) (Swiss Medical Weekly, 2022)
Pulmonary hypertension is an heterogeneous group of diseases characterised by increased pulmonary arterial pressures which impact on the upstream right ventricle. Pulmonary hypertension can be challenging to diagnose, classify and monitor when specific therapies are applicable. Cardiac magnetic resonance (CMR) imaging has greatly evolved in the last decades and is a promising tool to non-invasively follow pulmonary hypertension patients. CMR provides a comprehensive evaluation of the heart and is therefore the gold standard for quantification of right ventricular volumes, mass and function, which are critical for pulmonary hypertension prognosis. In addition, innovative MR techniques allow an increasingly precise evaluation of pulmonary haemodynamics and lung perfusion. This review highlights the main advantages offered by CMR in pulmonary hypertension and gives an overview of putative future applications. Although right heart catheterisation remains mandatory in the diagnostic algorithm, CMR could play an increasingly important role in the coming years in monitoring pulmonary hypertension patients.